(untitled) (Al-Academy, 2015)
Address the current research study " Symbol Significances in Fakhir Mohammad Paintings " in an attempt to detect signs of the icon in the artist’s fee . The research contains four chapters The first chapter of which the methodological framework for the search starting with the problem of the specific research and asking the following: Maaltold semantic code in fees Luxury Muhammad? As well as displaying the importance of research and the need for it and in order to search through ( you know the implications of the code in the fee Luxury Muhammad) and for the period of ( 1980-2010 ) in his works of art as well as identifying the search terms . In the second chapter , such as the theoretical framework , and contained three sections focus of attention in the first section on the concept of the significance and the second section included a review of the code in all of Iraq’s ancient art and Islamic art and philosophically and with psychologists ( school of psychoanalysis ) . The third section has focused his attention on the icon in the modern European art and symbol in contemporary Iraqi art and finally symbol in fees Luxury Mohammed . While singled out the third quarter , the research procedures in terms of the research community and inventory tool , which included the collection of information Vtm adoption of a random sample of it and it was the number (3) works of art covered the limits of search adoption descriptive analytical method . Finally, the fourth quarter included the results , discussion and conclusions , as well as recommendations and suggestions Among the findings by the researcher are:1-is a symbol and a means of expression is not directly appropriate meanings or ideas with abstract character 2-Code related psychology of the artist and his inclinations and his vision of self , artist necessarily carries the character of his time.3-the symbol of a dynamic moving with the content of a variable takes new meaning with all the work depending on the Zmkane